2004
DOI: 10.1007/bf02734439
|View full text |Cite
|
Sign up to set email alerts
|

The effects of estradiol on avoidance learning in ovariectomized adult rats

Abstract: The present study examined the effects of ovariectomy and subsequent estradiol replacement on learning in young adult rats using a set of instrumental avoidance paradigms differing in the nature and extent of prior experience in the learning context. Thus, one group of animals was placed directly into avoidance learning (AV). A second group was trained on an appetitive task first, and then transferred into the aversive context (AP-AV). The third group was exposed to the training context without any specific ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Adult female Long-Evans Hooded rats ( n = 12) were ovariectomized (OVX) using methods previously employed in our laboratory (Goodman et al 2004). Briefly, female rats were anesthetized with isoflurane gas, and 2 cm incisions were made bilaterally at the dorsal/ventral midsection just posterior to the ribcage, extending through the muscle wall.…”
Section: Methodsmentioning
confidence: 99%
“…Adult female Long-Evans Hooded rats ( n = 12) were ovariectomized (OVX) using methods previously employed in our laboratory (Goodman et al 2004). Briefly, female rats were anesthetized with isoflurane gas, and 2 cm incisions were made bilaterally at the dorsal/ventral midsection just posterior to the ribcage, extending through the muscle wall.…”
Section: Methodsmentioning
confidence: 99%
“…Estradiol influences many types of learning and memory processes (Luine et al, 1998; Goodman et al, 2004; Leuner et al, 2004; Inagaki et al, 2010; Cover et al, 2014), and studies examining estradiol’s effects on neurogenesis, dendritic branching, and long-term potentiation have demonstrated that it can alter brain structure and function as well (Galvin and Ninan, 2014; Mahmoud et al, 2016; Srivastava et al, 2013). Given the higher prevalence of fear and anxiety disorders in women compared to men, a better understanding of how estradiol can affect the neural substrates and mechanisms that control fear responses is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…These dramatic fluctuations in circulating estrogens likely affect neural processing. Indeed, numerous effects of estrogens on neuronal function as well as synaptic remodeling have been documented (Flanagan-Cato, 2000; Goodman et al, 2004; King and Seiler, 1988; Kurunczi et al, 2009; Luine et al, 1998; Parducz et al, 2006; Spencer et al, 2008; Zurkovsky et al, 2006; Zurkovsky et al, 2007). Moreover, effects on neural processes induced by the profound loss of circulating estrogens following ovariectomy have also been reported (Beltran-Campos et al, 2011; Das et al, 2002; King and Seiler, 1988; Vaucher et al, 2001).…”
Section: Introductionmentioning
confidence: 99%